Biological Approaches Integrating Algae and Bacteria for the Degradation of Wastewater Contaminants—A Review - Mathew, Merwin Mammen; Khatana, Kanchan; Vats, Vaidehi; Dhanker, Raunak; Kumar, Ram; Dahms, Hans-Uwe; Hwang, Jiang-Shiou (Frontiers in Microbiology, 2022)
The traditional approach for biodegradation of organic matter in sewage treatment used a consortium of bacterial spp. that produce untreated or partially treated inorganic contaminants resulting in large amounts of poor-quality sludge. The aeration process of activated sludge treatment requires high energy. So, a sustainable technique for sewage treatment that could produce less amount of sludge and less energy demanding is required for various developed and developing countries. This led to research into using microalgae for wastewater treatment as they reduce concentrations of nutrients like inorganic nitrates and phosphates from the sewage water, hence reducing the associated chemical oxygen demand (COD). The presence of microalgae removes nutrient concentration in water resulting in reduction of chemical oxygen demand (COD) and toxic heavy metals like Al, Ni, and Cu. Their growth also offers opportunity to produce biofuels and bioproducts from algal biomass. To optimize use of microalgae, technologies like high-rate algal ponds (HRAPs) have been developed, that typically use 22% of the electricity used in Sequencing Batch Reactors for activated sludge treatment with added economic and environmental benefits like reduced comparative operation cost per cubic meter, mitigate global warming, and eutrophication potentials. The addition of suitable bacterial species may further enhance the treatment potential in the wastewater medium as the inorganic nutrients are assimilated into the algal biomass, while the organic nutrients are utilized by bacteria. Further, the mutual exchange of CO2 and O2 between the algae and the bacteria helps in enhancing the photosynthetic activity of algae and oxidation by bacteria leading to a higher overall nutrient removal efficiency. Even negative interactions between algae and bacteria mediated by various secondary metabolites (phycotoxins) have proven beneficial as it controls the algal bloom in the eutrophic water bodies. Herein, we attempt to review various opportunities and limitations of using a combination of microalgae and bacteria in wastewater treatment method toward cost effective, eco-friendly, and sustainable method of sewage treatment.